Anti-Neospora caninum and anti-Sarcocystis spp. specific antibodies cross-react with Besnoitia besnoiti and influence the serological diagnosis of bovine besnoitiosis - García Lunar, P. (2015)
Bovine besnoitiosis control remains a challenge because the disease continues to spread and control relies solely on accurate diagnosis coupled to management measures. However, recent studies have reported that routinely used ELISAs may raise a high number of false-positive results. Herein, cross-reactions between Besnoitia besnoiti antigens and anti-Neospora caninum and/or anti-Sarcocystis spp.-specific antibodies were studied in an in house ELISA since N. caninum and Sarcocystis spp. are closely related parasites, and both infections are highly prevalent in cattle worldwide. The serum panel was composed of the following categories: sera from B. besnoiti-seronegative (n=75) and -seropositive cattle (n=66), B. besnoiti-based-ELISA false-positive reactors (n=96) together with N. caninum (n=36) and Sarcocystis spp. (n=42) -seropositive reference cattle sera. B. besnoiti tachyzoite based western blot (WB) results classified animals as seropositive or seronegative. Sera were analyzed for the detection of anti-N. caninum by WB and ELISA and anti-Sarcocystis spp.-specific antibodies by WB and IFAT. Those samples recognizing a Sarcocystis spp. 18-20kDa antigenic region and N. caninum 17-18kDa immunodominant antigen were considered to be Sarcocystis spp. and N. caninum seropositive, respectively. The category of B. besnoiti based-ELISA false-positive reactors showed the highest number of sera with specific anti-Sarcocystis spp. and anti-N. caninum antibodies (74%; 71/96), followed by the N. caninum-seropositive cattle category (52.8%; 19/36). In contrast, few B. besnoiti-seronegative and -seropositive cattle showed antibodies against Sarcocystis spp. and N. caninum (10.7%; 8/75 and 1.5%; 1/66), respectively). This study revealed that B. besnoiti false-positive ELISA results were associated not only with the presence of anti-N. caninum and anti-Sarcocystis spp. antibodies (χ2: 78.36; p<0.0001; OR: 34.6; CI: 14-88) but also with high antibody levels against them using ELISA and IFAT tests, respectively (p<0.05; t-test). These results may explain why only some animals seropositive to Sarcocystis spp. and/or N. caninum are Besnoitia false-positive reactors. Therefore, sera meeting these requirements should be included in future validations of serological tests for bovine besnoitiosis.